Varnost v lokalnih skupnostih – multidisciplinarne perspektive (University of Maribor Press, 2024)
Safety and Security in Local Communities - A Multidisciplinary Perspective. This book on multidisciplinary perspectives on security in local settings presents the work of the researchers of the Security in Local Communities - Comparing Rural and Urban Settings (2019-2024) programme group. The book comprises five parts: on the work of the programme group and the multidisciplinary and multiple perspectives of security in local settings, urban and rural perspectives on security, policing and policing and stakeholders in security provision in local settings, multiculturalism and responding to security risks, and cybersecurity in local communities. The contributions cover the following topics: security research, national and human security, public opinion on security, social ties and solidarity, rural criminology, feelings of security, juvenile delinquency, self-perception of police legitimacy, police performance, the organisation of municipal police forces and the cooperation of police forces with other security actors, Roma issues, vigilante groups, cyber-security, and offences against law and order on the internet.